2020
DOI: 10.14744/eej.2020.99609
|View full text |Cite
|
Sign up to set email alerts
|

Root and Canal Configuration of Mandibular First Molars in a Yemeni Population: A Cone-beam Computed Tomography

Abstract: To describe root and canal morphology of mandibular first molars (MFMs) in a Yemeni population using cone-beam computed tomography (CBCT). Methods: CBCT images of 500 right and left untreated MFMs with fully developed roots from 250 Yemenis (125 male and 125 female) comprised the sample size of this study. The following characteristics were recorded: (1) number of roots and their type and morphology, (2) number of canals orifices per root, (3) type of canal configuration and (4) primary variations in the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
5
5
1
Order By: Relevance
“…is implies that most of the first molars in the Saudi population have three canals. is finding is in agreement with the research conducted by Mashyakhy et al on the Saudi population [20], Abarca et al on the Palestinian population [36], and Senan et al on the Yemeni subpopulation [40]. In another study published by Silva et al [41] on CBCT images of mandibular first and second molars of a Brazilian population, the first molars had two separate roots (74%) with a greater occurrence of two canals in the mesial root and one canal in the distal root.…”
Section: Discussionsupporting
confidence: 93%
“…is implies that most of the first molars in the Saudi population have three canals. is finding is in agreement with the research conducted by Mashyakhy et al on the Saudi population [20], Abarca et al on the Palestinian population [36], and Senan et al on the Yemeni subpopulation [40]. In another study published by Silva et al [41] on CBCT images of mandibular first and second molars of a Brazilian population, the first molars had two separate roots (74%) with a greater occurrence of two canals in the mesial root and one canal in the distal root.…”
Section: Discussionsupporting
confidence: 93%
“…This range is in accordance with the result of the current study. The prevalence of RE was higher in female3.42% then in male 2.91% but with no significance difference which in accordance with other studies (20,8) . In concurrency to previous studies in the literature which reported significant difference Regarding to gender (26) .…”
Section: Discussionsupporting
confidence: 90%
“…Limited numbers of previous studies estimate the prevalence of RE among Arab population. As the prevalence were 3% in Sudanese,2.9% in Saudi Arabian population, 3.052%in Yemeni population and 3.73% in Palestinian population (7,11,12,20) . This finding were in accordance with the result of current study which reported 3.12% for the prevalence of RE.…”
Section: Discussionmentioning
confidence: 89%
“…Various populations when studied for gross root morphology of maxillary premolar teeth showed wide variation among maxillary 1 st premolar teeth 11,12 , but 2 nd premolar teeth has consistent morphology in most populations. Table-V explains variation of maxillary 1 st premolar root morphology among various populations worldwide.…”
Section: Discussionmentioning
confidence: 98%